Prediction error for free monetary reward in the human prefrontal cortex. - Ramnani, N; Elliott, R; Athwal, B; Passingham, R (2004)
Making predictions about future rewards is an important ability for primates, and its neurophysiological mechanisms have been studied extensively. One important approach is to identify neural systems that process errors related to reward prediction (i.e., areas that register the occurrence of unpredicted rewards and the failure of expected rewards). In monkeys that have learned to predict appetitive rewards during reward-directed behaviors, dopamine neurons reliably signal both types of prediction error. The mechanisms in the human brain involved in processing prediction error for monetary rewards are not well understood. Furthermore, nothing is known of how such systems operate when rewards are not contingent on behavior. We used event-related fMRI to localize responses to both classes of prediction error. Subjects were able to predict a monetary reward or a nonreward on the basis of a prior visual cue. On occasional trials, cue-outcome contingencies were reversed (unpredicted rewards and failure of expected rewards). Subjects were not required to make decisions or actions. We compared each type of prediction error trial with its corresponding control trial in which the same prediction did not fail. Each type of prediction error evoked activity in a distinct frontotemporal circuit. Unexpected reward failure evoked activity in the temporal cortex and frontal pole (area 10). Unpredicted rewards evoked activity in the orbitofrontal cortex, the frontal pole, parahippocampal cortex, and cerebellum. Activity time-locked to prediction errors in frontotemporal circuits suggests that they are involved in encoding the associations between visual cues and monetary rewards in the human brain.